Problematika Implementasi Pembelajaran Tematik Integratif di Lembaga Pendidikan Dasar Islam: Studi Kasus di Madrasah Ibtidaiyah Negeri (MIN) Garahan Jember Jawa Timur - Usriyah, Lailatul; Prayogo, M. Suwignyo (State Islamic Institute of Madura, 2018)
Abstract Developing and changing of education curriculum will affect the learning process significantly in formal education institution such as elementary school or madrasah. The presence of thematic learning in an elementary school or madrasah is a form of changing in implementation of curriculum 2013 which have many problems in the implementation as faced by some teacher in Ibtidaiyah Garahan or now called MIN 4 Jember.The study aims to describe the implementation processes, problems, and solutions for the implementation of integrated thematic learning in MIN Garahan Jember. The study applied the qualitative research focus on case study design.The results of the study includes : 1) the implementation of thematic learning in MIN Garahan including planning, implementing, and evaluating; 2) the problems of integrated thematic learning in MIN Garahan Jember including: a. learning method, b. class management, c. the use of media that have not maximized, d. the difficulty of assessment process faced by almost all teachers, e. inadequate learning sources; 3) the strategy of Madrasah in implementing the integrated thematic learning effectively in MIN Garahan consisting: developing the teacher competence through training, seminar and workshop activities, developing facility and learning sources, cooperating with the stakeholders, activating the role of Madrasah committee, using the variety and fun learning strategy. Keywords: The Problems, Implementation of Integrated Thematic Learning